If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ac + -2b = 9c Solving ac + -2b = 9c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. ac + -2b + 2b = 2b + 9c Combine like terms: -2b + 2b = 0 ac + 0 = 2b + 9c ac = 2b + 9c Divide each side by 'c'. a = 2bc-1 + 9 Simplifying a = 2bc-1 + 9 Reorder the terms: a = 9 + 2bc-1
| 3(1+2x)=21 | | 7(9+6x)=-441 | | 4x-2(-2y+5x)+6y= | | 5y+8n= | | 6(-8-5x)=-168 | | 1=b/3-7 | | 5(x+1)-7.5x=-2 | | 8=192 | | -3/14y=-15 | | 0=-16t^2+160t+3 | | 81g=3564 | | 37t=3478 | | 8n-8m/16n-16m | | 56w=4648 | | 106=6x+7x+2 | | 60m=4020 | | 83j=5644 | | 8t(6t+2)+t(4t+3)= | | *2x-3**5x+6*= | | Log(X)9=(1/2) | | 11!11!/13!14! | | 3c+7.25=4.72 | | 74e=1258 | | 3w-18*w=244 | | -4(3+7x)=-180 | | n^2+15n+57=0 | | 17p=1326 | | 50k=2650 | | 1,816,168.016=4/3*3.14*x^3 | | 1,816,168.016=4/3*3.14*r^3 | | 36*67= | | 68a=3332 |